Capital flows and economic fluctuations : the role of commercial banks in transmitting shocks - Zhou, Yong Sarah (IMF [Washington]US, 2008)
Examines the central role played by commercial banks in intermediating and amplifying the capital flow shocks to the local economy in the 1997 Asia financial crisis.